COMPARAÇÃO DE MEDIDAS CEFALOMÉTRICAS DOS ESPAÇOS AÉREOS NASO E OROFARÍNGEO ENTRE RESPIRADORES NASAIS E ORAIS - Murakami, Luciano Kazuo (2011)
The literature has shown that the altered breathing mode influences the structural and functional aspects of the stomatognathic system. Aim: To compare the cephalometric measurements of nasal and oropharyngeal air spaces among nasal breathers and with breathing mode altered (oral or oronasal). Method: This exploratory and retrospective study, used the medical records of patients treated at the Clinic of Orthodontics, in the period from 2000 to 2009, and the 87 patients (malocclusion, Angle Class I) who comprised the sample, 55 were nasal breathers (NB) and 32 had breathing mode altered (ONB - oronasal or oral), 47 were female and 40 were male, aged between 8.75 and 22 years old (average 14.78 years old). We analyzed the lateral cephalograms, not undergoing orthodontic treatment or previous speech therapy. The analysis variables were: age, sex, race, breathing mode and analysis of nasal and oropharyngeal spaces by the method adopted by Zanelato. Through statistical analysis (Student t test and chi-square), the results were interpreted as to its significance. Results: There were significant statistical differences in age groups (NB>ONB), the prevalence of men (higher in ONB group), leukoderma in both groups, supero-anterior airway (lower in ONB group) and tonsil (higher in ONB group), and tonsil size in melanoderma. The other variables analysis showed no statistically significant differences. Conclusion: The cephalometric measurements of the nasopharyngeal space (lower in ONB group) and tonsil (higher in ONB group) differed between groups and the oropharyngeal space did not differ between groups. Other factors than just the space and nasopharyngeal tonsil, may predispose individuals to the oronasal breathing or predominantly oral breathing and the orthodontist, in his clinical practice, can objectively evaluate the particularities of each case and, therefore, proceed to the most appropriate action as early as possible.